Preliminary Magnetization Pattern Study On Magnetic Gear - Mohd Ab Halim, Mohd Firdaus; Raja Othman, Raja Nor Firdaus Kashfi; Sulaiman, Erwan (World Academy of Research in Science and Engineering, 2020)
In this paper, radial anisotropic, circumferential anisotropic, parallel circular direction (PCD) and parallel radial direction (PRD) magnetization pattern are introduced and explained. Then, these magnetization pattern are simulated using JMAG Designer 16.0 on the coaxial magnetic gear with 2.33 gear ratio. Torque and efficiency are calculated and compared. The result shows that the radial anisotropic produce the highest torque and register the best efficiency versus the latter.With this study, it is hope that the designer can have second option to choose other type of magnetization without sacrificing the performance. The option may become in handy when the RAP becomes more expensive or difficult to procure